THE IMPACT OF BRAND IDENTITY AND PRICE ON YOUNGER CUSTOMERS’ SATISFACTION WITH FOOD TRUCKS IN TERENGGANU - Norazlina binti Rahmat; NurFarzana Athirah binti Rohaizad; Intan Liana binti Ibrahim; Norzaidah binti Ngali (International Journal of Accounting, Finance and Business, 2022)
A food truck is becoming a global business trend and is rapidly growing in Malaysia. Food truck owners are working tirelessly to achieve customer satisfaction through superior brand identity and offering competitive prices to make food trucks more recognizable and interesting to visit, especially among the younger generation. This study aims to analyze the effect of brand identity and price on younger customers’ satisfaction. An online survey through Google Form was used to collect data. The convenient sampling was chosen, and 124 samples of the younger generation who visited or purchased from food trucks in Terengganu are involved in this study. The findings provide evidence that brand identity and price had a positively significant impact on younger customers’ satisfaction with food trucks. It will assist food truck owners to improve their brand identity and pricing strategies to increase customer satisfaction, encourage existing customers to return, and attract potential customers